The preposition under and its noun collocates in the under-NOUN pattern: A quantitative corpus-based investigation - Jarosław Wiliński (Crossroads, 2020)
This paper adopts a usage-based perspective on grammatical structure (Goldberg 2006, 2013) and the attraction-reliance measure (Schmidt 2000; Schmid & Küchenhoff 2013) to gauge the reciprocal interaction between a noun and the preposition under in the under-NOUN pattern: in other words, to determine strongly attracted nouns of this preposition. On the basis of the data extracted from the academic part of the Corpus of Contemporary American English (COCA), this paper seeks to show that there are nouns that are more strongly attracted to the preposition under than others and that the co-occurrences of particular nouns with this preposition are more significant than others. In addition, the results of the analysis seem to suggest that the mutual associations between particular nouns and this preposition depend upon different senses of under and are therefore motivated by conceptual metaphors, metonymies, and/or image schemas.